2008
DOI: 10.1007/s00104-008-1546-2
|View full text |Cite
|
Sign up to set email alerts
|

Rektumprolaps

Abstract: Surgical treatment of rectal prolapse aims to correct morphology and restore function. Many techniques are available, but none can be considered a gold standard. Abdominal approaches differ with regard to abdominal access, extent of rectal mobilisation, technique of rectal pexy, and concomitant sigmoid resection. Local (perineal/transanal) procedures plicate or resect the rectum. The choice of operative approach is based on the patient's condition and expected outcome of the procedure, e.g. recurrence rate, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
(12 reference statements)
1
7
0
3
Order By: Relevance
“…Much like our data, many studies reported satisfactory rates of improvement of constipation with 82% [26], 62% [27], and 69% [24] after LRR. Equally, incontinence can be effectively improved by the procedure as shown by the current study as well as by others [9,13]. Improvement rates for both continence and constipation after Delorme's procedure only rarely exceed 50%, regardless of age [9,13].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Much like our data, many studies reported satisfactory rates of improvement of constipation with 82% [26], 62% [27], and 69% [24] after LRR. Equally, incontinence can be effectively improved by the procedure as shown by the current study as well as by others [9,13]. Improvement rates for both continence and constipation after Delorme's procedure only rarely exceed 50%, regardless of age [9,13].…”
Section: Discussionsupporting
confidence: 55%
“…Improvement rates for both continence and constipation after Delorme's procedure only rarely exceed 50%, regardless of age [9,13]. Outcome for improvement of incontinence is generally slightly better in other perineal operations such as Altemeier's procedure, whereas improvement of constipation is almost never significant [9,13].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations